2022 18th International Conference on Synthesis, Modeling, Analysis and Simulation Methods and Applications to Circuit Design ( 2022
DOI: 10.1109/smacd55068.2022.9816287
|View full text |Cite
|
Sign up to set email alerts
|

On the use of an RTN simulator to explore the quality trade-offs of a novel RTN-based PUF

Abstract: Physical Unclonable Functions (PUFs) use variability as an entropy source from which to generate secure authentication and identification. While most silicon PUFs exploit the well-known Time-Zero Variability of CMOS technologies, the lack of efficient simulation tools for the Time-Dependent Variability (TDV) has left the potential benefits of this other kind of variability largely unexplored. However, recent advances in the field are allowing this exploration to begin. The objective of this paper is then to ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A relationship between transistor size and the optimum value of the current ICC is defined. Since the transistors used in this work have the size ratio W/L = 80nm/60nm, following the indications described in [10], the optimum ICC should be 100nA. All in all, the MVF captures, as the MCF does, the RTN in the transistor by subtracting the maximum envelope (CMAXV) and the minimum envelope (CMINV) over a period of time.…”
Section: A Voltage-mode Version Of the Rtn-pufmentioning
confidence: 99%
See 1 more Smart Citation
“…A relationship between transistor size and the optimum value of the current ICC is defined. Since the transistors used in this work have the size ratio W/L = 80nm/60nm, following the indications described in [10], the optimum ICC should be 100nA. All in all, the MVF captures, as the MCF does, the RTN in the transistor by subtracting the maximum envelope (CMAXV) and the minimum envelope (CMINV) over a period of time.…”
Section: A Voltage-mode Version Of the Rtn-pufmentioning
confidence: 99%
“…The quality of the RTN-PUF has been demonstrated in [6] and design preliminaries were discussed in [10] [11]. It was found that, for the 65-nm CMOS technology used as a case study, minimum-size PMOS transistors (W/L = 80nm/60nm) yielded a better PUF response quality.…”
Section: Introductionmentioning
confidence: 99%